Angioleiomyoma of the Auricle: An Unusual Tumor on a Rare Location - Jean Kanitakis (Case Reports in Otolaryngology)
Cutaneous angioleiomyomas (ALMs) (also known as vascular leiomyomas or angiomyomas) are unusual benign tumors of the skin deriving from the muscle layer of dermal blood vessels. They usually manifest as tender subcutaneous nodules, mostly encountered on the legs of adult women in their fifth or sixth life decade. ALMs rarely develop on the head/neck area, and even more rarely (<3% of all cases) on the auricle. Head/neck (including ear) ALMs differ from their more usual leg counterparts in that they are usually painless and do not show a female predominance. The diagnosis is clinically difficult, and most cases are diagnosed by histopathologic examination. A new case of an auricular ALM in a 40-year-old Caucasian man is reported herein, and a brief literature review on this unusual tumor is presented.